THE INFLUENCE OF HEALTH EDUCATION THROUGH AUDIOVISUALMEDIA ON THE IMPLEMENTATION OF GYMNASTICS EYES ONTEENAGERS AT SMAN XI SURABAYA - Wahyuningsih, Binarti Dwi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Using a smartphone for hours makes the eyes tired and vision becomes blurry. Eye exercise therapy can improve eye health, with a series of movements by the eye organs thereby increasing eye sharpness. Health education can change unhealthy behavior into healthy behavior, so audiovisual media is needed to support the learning process. The aim of this research is to prove the influence of health education through audiovisual media on the implementation of eye exercises among teenagers at SMAN XI Surabaya. The research method used was pre-experimental with a one group pre test post test design. The population of all class X students at SMAN XI Surabaya is 426 students. The sampling technique used in this research was simple random sampling so that the sample obtained was 43 students. The instrument in this research is an observation sheet. Based on the results of the chi square test analysis, it was found that the p value = 0.000 and α < 0.05, so this shows p < α, which means this research shows that there is an influence of health education through audiovisual media on the implementation of eye exercises among teenagers at SMAN XI Surabaya. The respondent's ability to do eye exercises was because the respondent had been given health education. Delivering health education using audiovisual media can provide a lot of stimulus to students, because the nature of audiovisuals is that it combines sound and images, making it easier for students to do eye exercises independently.